AN ANALYSIS OF NATIONAL SANITARY VETERINARY AND FOOD SAFETY AUTHORITY (ANSVSA)`S ACTIVITIES DURING THE 2023 SUMMER SEASON IN CONSTANTA COUNTY, ROMANIA - Iuliana CONDULEÈš; Silvius STANCIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper presents an analysis of the actions undertaken by the ANSVSA inspectors during the 2023 summer season in the areas of tourist interest within Constanta County. Based on the analyzed data concerning the Summer Season Command period and the periods and areas overcrowded with tourists, specifically from June 26, 2023, to September 3, 2023, several conclusions can be drawn: The research highlights the fact that food business operators still require support in order to meet food safety standards and to comply with the legislation in force. These issues have resulted in increased inspections in order to prevent food safety risks, including the prevention of food poisoning. A total of 2,245 units were inspected, leading to the enforcement of 47 penalties for offences, totaling 4,962,200 RON, and over 2 tons of non-compliant food were confiscated. These conclusions provide an overview of the evolution of the activities conducted by food business operators in the South-East Region of Romania, indicating both the challenges to and opportunities for their development and the continued implementation of good hygiene and food safety practices.